Results of Operational Sea-Wave Monitoring with Radar Gauges - Rütten, Sebastian; Mai, Stephan; Wilhelmi, Jens; Zenz, Theodor; Hein, Hartmut; Barjenbruch, Ulrich (The International Hydrographic Review, 2013)
The German Federal Institute of Hydrology (BfG) developed a low-cost, non-contact sea-wave monitoring system based on a single radar sensor. A short description of the measuring system and the analysis of wave parameters is given. Furthermore, long-term wave measurements with this system, in combination with wind-measurements and statistics, are used to analyse possible future changes in wave heights. The results are in good agreement with those of other methods. Due to the good results achieved with the single radar sensor, an extension of the system which will be capable of recording directional information, is now under development. First results are presented in this study.